Analysis of the Vibration Characteristic of 2F2R Macro-micro Manipulator based on Cam Curve Theory - Gao Sheng; Zhao Xuan; Zhang Piaoshi; Yang Shuai; Ren Fushen (Jixie chuandong)
Taking the 2F2R macro micro manipulator as study object,its model is established by using the finite element method. Based on the cam curve theory,the equations of motion curve such as the acceleration,the 5 degree polynomial,the deformed trapezoid,the cycloid,the synthetic sine,and the deformed sine are derived in detail. Based on the above two aspects of works,the effect and rule of different motion curves on the elastic vibration of manipulator end are studied,which has a good reference value for the trajectory planning of this type of manipulator.